2003
DOI: 10.1242/jcs.00252
|View full text |Cite
|
Sign up to set email alerts
|

The pairing of X and Y chromosomes during meiotic prophase in the marsupial species Thylamys elegans is maintained by a dense plate developed from their axial elements

Abstract: Unlike eutherian males, pairing of the sex chromosomes in marsupial males during the first meiotic prophase is not mediated by a synaptonemal complex. Instead, a specific structure, the dense plate, develops during pachytene between the sex chromosomes. We have investigated the development and structural nature of this asynaptic association in males of the marsupial species Thylamys elegans by means of immunolabelling and electron microscopy techniques. Our results show that the behaviour of male marsupial sex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
73
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(77 citation statements)
references
References 36 publications
(63 reference statements)
4
73
0
Order By: Relevance
“…Unequal crossover has been suggested to explain sex chromosome-specific amplification of constitutive heterochromatin seen in rodents (Nova et al 2002). The marsupial X and Y do not undergo homologous pairing (side to side) at meiosis; however, axial pairing (end to end) does occur (Solari and Bianchi 1975;Sharp 1982;Page et al 2003). Although no pseudoautosomal region has been identified on marsupial sex chromosomes , the X and Y of Macropus eugenii have been shown to possess homologous sequences (Toder et al 1997b).…”
Section: Discussionmentioning
confidence: 99%
“…Unequal crossover has been suggested to explain sex chromosome-specific amplification of constitutive heterochromatin seen in rodents (Nova et al 2002). The marsupial X and Y do not undergo homologous pairing (side to side) at meiosis; however, axial pairing (end to end) does occur (Solari and Bianchi 1975;Sharp 1982;Page et al 2003). Although no pseudoautosomal region has been identified on marsupial sex chromosomes , the X and Y of Macropus eugenii have been shown to possess homologous sequences (Toder et al 1997b).…”
Section: Discussionmentioning
confidence: 99%
“…According to this, the dense plate is mainly formed by the SYCP3 component of the AEs (Fig. 4c,d) (Page et al 2003). It is interesting to note that although the cohesin subunits SMC3 and STAG3 are present along sex chromosomes, they do not follow many of the modifications of the sex chromosomal AEs and, most relevantly, do not participate in the organization of the dense plate .…”
Section: Marsupial Sex Chromosomal Aes Expand At Their Ends To Form Amentioning
confidence: 91%
“…The modification of the AEs that originates the dense plate in marsupial males is indicative that the structural elements of the SC may play, in addition to the organization of the canonical LEs, other roles in nonhomologous chromosomes pairing (Page et al 2003) and segregation (Page et al unpublished). These additional roles of the SC elements are not exclusive of marsupial meiosis.…”
Section: Marsupial Sex Chromosomal Aes Expand At Their Ends To Form Amentioning
confidence: 99%
“…In mouse, a meiosis-specific structural protein, Sycp3, which appears in axial and lateral elements of the SC, is involved in the monopolar attachment of sister kinetochores during the first meiotic division (Parra et al 2004). Recently, Page et al (2003Page et al ( , 2005 have reported that in marsupial males the pairing of the achiasmatic X and Y chromosomes during meiotic prophase is maintained by a dense plate developed from their axial elements.…”
Section: Discussionmentioning
confidence: 99%